2018
DOI: 10.3389/fimmu.2017.01895
|View full text |Cite
|
Sign up to set email alerts
|

Monocytic Myeloid-Derived Suppressor Cells in Chronic Infections

Abstract: Heterogeneous populations of myeloid regulatory cells (MRC), including monocytes, macrophages, dendritic cells, and neutrophils, are found in cancer and infectious diseases. The inflammatory environment in solid tumors as well as infectious foci with persistent pathogens promotes the development and recruitment of MRC. These cells help to resolve inflammation and establish host immune homeostasis by restricting T lymphocyte function, inducing regulatory T cells and releasing immune suppressive cytokines and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
133
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(137 citation statements)
references
References 170 publications
(290 reference statements)
3
133
0
1
Order By: Relevance
“…Myeloid‐derived suppressor cells (MDSCs) are another population of macrophages that originate from myeloid progenitors . While MDSCs are known to remain arrested in an immature state of macrophage differentiation, accumulating evidence clearly demonstrates their role in suppression of T‐cell responses during infection . In addition to their direct suppressive effects on adaptive immune responses, MDSCs can also affect other subsets of macrophages by modulating their cytokine production …”
Section: The Diversity Of Macrophages and Their Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myeloid‐derived suppressor cells (MDSCs) are another population of macrophages that originate from myeloid progenitors . While MDSCs are known to remain arrested in an immature state of macrophage differentiation, accumulating evidence clearly demonstrates their role in suppression of T‐cell responses during infection . In addition to their direct suppressive effects on adaptive immune responses, MDSCs can also affect other subsets of macrophages by modulating their cytokine production …”
Section: The Diversity Of Macrophages and Their Functionsmentioning
confidence: 99%
“…MDSCs are known to remain arrested in an immature state of macrophage differentiation, accumulating evidence clearly demonstrates their role in suppression of T-cell responses during infection. 28 In addition to their direct suppressive effects on adaptive immune responses, MDSCs can also affect other subsets of macrophages by modulating their cytokine production. 29 In recent years, it has become evident that cytokines and chemokines produced by immune and nonimmune cells in bone marrow can also induce heterogeneity in macrophage populations via activation of hematopoietic stem cells (HSCs).…”
Section: Whilementioning
confidence: 99%
“…Treg-depletion has only a minor effect, whereas T-cell proliferation remains inhibited despite the absence of B220 + and CD11c + cells 7 . Nevertheless, T-cell suppression in chronically infected mice has been associated with the expansion of monocytic-like (CD11b + Ly6C + Ly6G low phenotype), neutrophilic-like (CD11b + Ly6C low Ly6G + phenotype) and eosonophilic-like (CD11b + Ly6C low Ly6G low phenotype) MDSCs 7;8;9;10;11 , affirming the dominant immunosuppressive role of MDSCs during chronic S. aureus infections.…”
mentioning
confidence: 90%
“…106 For transplantation tolerance, perioperative recipient infusion of MDSCs has been shown to prolong allograft survival in mouse islet transplantation, 107 corneal transplantation 108 and skin transplantation. 110,111 On the other hand, we have recently shown that CMV infection in a murine model indeed impairs MDSC differentiation, thereby breaking transplantation tolerance mediated by MDSCs. On the one hand, both G-MDSCs and M-MDSCs have been shown to expand postinfection, which in turn inhibits subsequent T cell immune responses.…”
Section: Myeloid Derived Suppressor Cells (Mdscs)mentioning
confidence: 99%
“…On the one hand, both G-MDSCs and M-MDSCs have been shown to expand postinfection, which in turn inhibits subsequent T cell immune responses. 110,111 On the other hand, we have recently shown that CMV infection in a murine model indeed impairs MDSC differentiation, thereby breaking transplantation tolerance mediated by MDSCs. 112 Acute CMV infection is found to inhibit G-MDSC expansion and impair the suppressive function of M-MDSCs.…”
Section: Myeloid Derived Suppressor Cells (Mdscs)mentioning
confidence: 99%